GEOGRAPHICAL AND INDIVIDUAL DETERMINANTS OF RURAL OUTMIGRATION TO A TROPICAL FOREST PROTECTED AREA: THE MAYA BIOSPHERE RESERVE, GUATEMALA - David Lopez-Carr; Aracely Martinez; Richard E. Bilsborrow; Thomas M. Whitmore (European Journal of Geography)
Migration necessarily precedes deforestation in tropical agricultural frontiers. Therefore, identifying individual, household and place characteristics (demographic, political, social, economic, and ecological) related to this process is crucial for understanding the drivers of tropical deforestation. This will in turn be useful for developing policies to reduce deforestation, which cannot be approached only from the destination end since this ignores the fundamental role played by migrant farmers advancing the agricultural frontier. This paper uses data from surveys conducted in areas of high out-migration, much to the agricultural frontier in northern Guatemala. Results suggest that larger family sizes, land scarcity, soil degradation, poor access to markets, low education, and poverty are linked to migration to the frontier in Guatemala.